Composición química de cuatro productos cárnicos de la ciudad de Iquitos para evaluar la energía requerida de procesamiento - Falla Linares, Yovany Jean Piero (2022)
The main objective of the present work of thesis was: evaluating the energy required of processing for each one of the four (4) meat productses (pig hamburger, hamburger of gamitana, hamburger of paiche and chicken hamburger) of the city of Iquitos. In the present investigation, the determination of the chemical composition was done (humidity, ash, fat, protein and carbohydrates) and was applicable Choi and Okos equations to determine the relations between the specific heat with temperature for each one of the four (4) mentioned meat products. Finally, the energy required of processing for the aforementioned meat products was evaluated. The results of the evaluation of he energy required of processing for each one of the four (4) meat products (pig hamburger, gamitana hamburger, paiche hamburger and chicken hamburger) of the city of Iquitos, were the following: 18857.7 kJ, 19054.8 kJ, 19438.4 kJ y 18994.3 kJ, respectively. This indicates that the meat product that requires bigger energy for his processing is paiche's hamburger. The evaluation of the energy required of processing, came true for 100 kg mass of meat product and once a status of temperature was incorporated into the specific heat of 20 to 80 °C.